2002
DOI: 10.1124/dmd.30.7.831
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Michaelis Constants for Cytochrome P450-Mediated Biotransformation Reactions Using a Substrate Depletion Approach

Abstract: ABSTRACT:The Michaelis constant (K M ) for cytochrome P450-mediated drug biotransformation reactions can be an important parameter in understanding the potential for a drug to exhibit saturable metabolism in vivo and nonlinear dose-exposure relationships. K M values were measured for several drug biotransformation reactions using recombinant heterologously expressed human enzymes. These determinations were made using an approach of monitoring substrate loss ("in vitro t 1/2 " method) at multiple substrate conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 18 publications
4
159
0
Order By: Relevance
“…Ternary and quaternary complexes are thought to underlie complex kinetics exhibited by P450s. The concentrations used for protein crystallization are ϳ1000-fold greater than the K m for mesoridazine formation from thioridazine determined by Obach and Reed-Hagen (40). These authors noted that thioridazine exhibited a small tendency to exhibit biphasic character suggestive of two binding sites with the population of the second binding site occurring at the highest concentration of thioridazine examined, 40 M. The authors concluded that this effect was unlikely to be significant for in vivo exposure to thioridazine.…”
Section: Bmentioning
confidence: 84%
“…Ternary and quaternary complexes are thought to underlie complex kinetics exhibited by P450s. The concentrations used for protein crystallization are ϳ1000-fold greater than the K m for mesoridazine formation from thioridazine determined by Obach and Reed-Hagen (40). These authors noted that thioridazine exhibited a small tendency to exhibit biphasic character suggestive of two binding sites with the population of the second binding site occurring at the highest concentration of thioridazine examined, 40 M. The authors concluded that this effect was unlikely to be significant for in vivo exposure to thioridazine.…”
Section: Bmentioning
confidence: 84%
“…Although substitution of the N-octyl chain to the N-decyl chain did not change the stability against CYP2D6, the N-hexyl or N-dodecyl chain improved the CYP2D6 metabolic stability. For the determination of the K m values for imipramine, desipramine, amitriptyline, propranolol, dextromethorphan, and propafenone, the substrate depletion method (Obach and Reed-Hagen, 2002) was used. The final CYP2D6 protein concentration, substrate concentrations, and incubation times were set at 10 pmol/ml, 0.1, 0.3, 1, 3, 10, and 30 M, and 0, 3, 6, and 9 min, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the absence of authentic samples for the metabolites of imipramine, desipramine, amitriptyline, propranolol, dextromethorphan, and propafenone, the substrate depletion method (Obach and Reed-Hagen, 2002) was used for determination of the Michaelis constant (K m ) values for typical CYP2D6 substrates. The final CYP2D6 protein concentration and substrate concentrations were set at 10 pmol/ml and 0.1, 0.3, 1, 3, 10, and 30 M, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we measured the metabolism of fibrates in RLM and HLM by applying the cofactors NADPH and UDPGA individually and simultaneously, allowing us to determine the contributions of both pathways using the same approach and detection platform. The substrate depletion approach has been shown to be comparable to the product formation approach and is increasingly being used in enzyme kinetics studies [23,27,30]. Considering the diversity of metabolites formed from the metabolism of fibrates and the requirement for semi throughput in this study, it is impractical to monitor product formation; thus the substrate depletion approach is more appropriate in this context.…”
Section: Discussionmentioning
confidence: 99%
“…(1) proposed by Obach and ReedHagen [27] with Origin software (version 7.5, MicroCal Software, Inc., Piscataway, NJ, USA).…”
Section: Discussionmentioning
confidence: 99%